Parameter Biokimia dan Hematologi Sapi Bali Lepas Sapih yang diberi Ransum Energi Protein Bertingkat (BIOCHEMICAL AND HEMATOLOGICAL PARAMETERS OF WEANING BALI CATTLE FEEDED WITH LEVELED PROTEIN ENERGY RATION) - Dharmawan, Nyoman Sadra; Mahardika, I Gede; Suryani, Ni Nyoman; Andini, Ni Putu Mega; Dewi, Ade Kiki Sintya (Jurnal Veteriner, 2019)
The feeding system greatly influences the chemical values and blood parameters of livestock. Biochemical determination of serum constituents can provide valuable information about nutritional status and environmental factors that affect animal health. The purpose of this study was to determine the effect of animal feed formation which consisted of four types of rations with multilevel protein energy levels for total cholesterol, triglycerides and other routine blood parameters of the weaning female balinese cattle. The study was carried out by administering a ration formula for three months in 12 weaning female balinese cattle, aged nine months, body weight 101.3-104.3 kg. Randomized Block Design with four treatment was used in this research , e.g. A = PK 12% and ME 2000 kcal/kg; B = PK 13% and ME 2100 kcal/kg; C = PK 14% and ME 2200 kcal/kg; D = PK 15% and ME 2300 kcal/kg. Blood sampling was collected at the end of the experiment followed by examination of total cholesterol, triglycerides, and other routine hematological parameters in the laboratory. Examination of total cholesterol and triglycerides using the enzymatic colorimetry method. Measurement of routine blood parameters such as total erythrocytes, hemoglobin levels, hematocrit values, total leukocytes, neutrophils, eosinophils, basophils, lymphocytes, and monocytes using an automatic hematology analyzer.  The results obtained were total cholesterol: 122.0-146.33 mg/dl; triglycerides: 122.0-146.33 mg/dl. Meanwhile, the total erythrocytes are (6.6-7.0) x106 ìl; hemoglobin (10.3-11.3) g/dl; hematocrit (27.6-28.8)%; total leukocytes (7.8-10.3) x 103ìl; neutrophils (20,7-27,6%); eosinophils (0.08-0.3%); basophils (0.3-1.4%); lymphocytes (66.6-72.2%); monocytes (3.65.5%). All results are still in the normal cattle reference range. There were no significant differences (P>0.05) between treatments. It was concluded that the four ration formulas had no effect on total cholesterol, triglycerides, and other routine hematological parameters from the blood of the weaning female Bali cattle.